Clays and Clay Minerals, Vol.5 5, No.1, 89–95, 2007. - Komlo´si, Andrea; Kuzmann, Erno˝; Nagy, Noe´mi M.; Homonnay, Zolta´n; Kubuki, Shiro; Ko´nya, Jo´zsef (The Clay Minerals Society, 2007)
The effect of FeCl3 in acetonic medium on the structure of Na-bentonite was studied using X-ray diffraction (XRD), 57Fe Mo¨ ssbauer spectroscopy, X-ray fluorescence spectroscopy and infrared spectroscopy to describe the structure of the bentonite before and after treatment.In the samples treated with FeCl3, an increase in the basal spacing was found by XRD, while a new magnetically split component assigned to Fe3+ incorporated within the interlayer regions of montmorillonite showed up in the lowtemperature Mo¨ssbauer spectra.T he Mo¨ssbauer parameters observed were close to those of Fe oxyhydroxides, suggesting the presence of some kind of nanoparticles.These results show that the treatment with acetonic FeCl3 solution is an effective method for introducing Fe into montmorillonite in the form of Fe3+ accommodated in the interlayer region.The treated samples proved to be efficient Lewis catalysts in the acylation of aldehydes (benzaldehyde and 4-OH-benzaldehyde) by acetic acid anhydride.
Incorporation Of Fe In The Interlayer Of Na-bentonite Via Treatment With Fecl3 In Acetone
Clays and Clay Minerals, Vol.5 5, No.1, 89–95, 2007. Incorporation Of Fe In The Interlayer Of Na-bentonite Via Treatment With Fecl3 In Acetone. Andrea Komlo´si; Erno˝ Kuzmann; Noe´mi M. Nagy; Zolta´n Homonnay; Shiro Kubuki; Jo´zsef Ko´nya. DOI: 10.1346/CCMN.2007.0550107. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Bentonite; Clay; Interlayer; Iron; Infrared Spectroscopy; Mo¨ssbauer Spectroscopy; XRD; XRF